Leading courses: Academic leadership for course coordinators. Final report. - Jones, Sue; Ladyshewsky, Richard; Oliver, Beverley; Flavell, Helen (Curtin Institute of Technology, 2009)
This project developed and trialled an experiential academic leadership program at Curtin University, designed to enhance the leadership skills of Course Coordinators (those academic staff responsible for a course or program of study leading to a degree award) to enable them to ultimately improve the students' experience of learning.